IDENTIFICATION AND EXTRACTION PROCESS OF CARDIAC GLYCOSIDES FROM FOXGLOVE PLANTS - Susi Febrianti; Fathi Farhan; Juarfianti Juarfianti; Sabrina Audry Salfa; Rema Elviona; Ika Meruya Kusuma (Journal of Medical Genetics and Clinical Biology, 2024)
Foxglove (Digitalis spp.) is a plant known for its cardiac glycoside content, which has been used in medicine for centuries. Cardiac glycosides, such as digoxin and digitoxin, are the main components that have a therapeutic effect on the cardiovascular system. This research examines the cardiac glycoside content of various Digitalis species, with a focus on extraction methods, isolation and characteristics of these compounds. Methods used include high-performance liquid chromatography (HPLC), mass spectrometry (MS), and nuclear magnetic resonance (NMR). The analysis results showed that Digitalis purpurea and Digitalis lanata were the main sources of cardiac glycosides. Digoxin and digitoxin were isolated and identified as the main active components. Pharmacological studies show that this compound interacts with the sodium-potassium ATPase pump, which increases cardiac contractility and is used in the treatment of heart failure and arrhythmias. Cardiac glycosides from the foxglove plant play an important role in cardiovascular therapy. Further research is needed to develop more efficient extraction methods and understand the deeper mechanisms of action, as well as potential side effects associated with long-term use.